Contemporary Management of Aneurysmal Subarachnoid Hemorrhage: A Literature Review - Yeo, Nikki; Terrett, Luke; Gupta, Arun K. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Subarachnoid hemorrhage (SAH) results in significant morbidity and mortality, which leads to additional economic and psychological burden. Atraumatic SAH is normally secondary to a ruptured aneurysm. Diagnosis of aneurysmal subarachnoid hemorrhage (aSAH) is usually made by computed tomography (CT) of the head: noncontrast CT identifies the hemorrhage, and CT angiography identifies the aneurysm.The management of aSAH is focused on securing the aneurysm and prevention of secondary brain injury. Definitive treatment of the aneurysm is done by endovascular coiling or surgical clipping, which should be performed as soon as possible with avoidance of hypertension and strict blood pressure management prior to aneurysm securement. Routine use of nimodipine is recommended by international guidelines as a neuroprotectant. Common neurological complications of aSAH are hydrocephalus, seizures, vasospasm, and delayed cerebral ischemia (DCI). Detection of DCI, especially in patients with poor-grade aSAH, can be challenging. In addition to clinical examination, multiple radiological modalities can be used, with digital subtraction angiography being the gold standard but CT perfusion gaining an increasingly important role. Extracranial complications including cardiac dysfunction, pulmonary edema, and electrolyte abnormalities are common, causing significant morbidity and mortality.In this review, a PubMed literature search was conducted using the terms “subarachnoid hemorrhage” and “management,” with results limited to past 5 years. Journal articles were hand-selected by the authors based on relevance, and the references were reviewed to identify additional relevant publications. Historically important publications were also included.
Keywords: subarachnoid hemorrhage; management; aneurysm; vasospasm; delayed cerebral ischemia